Metabolic hijacking styles: a review of how viral life cycles dictate glucose metabolism reprogramming - Bie, Ziyi; Tan, Yixing; Ye, Chun; Wei, Ke (Frontiers in Microbiology, 2025)
Viral infection profoundly reprograms host glucose metabolism to support replication. This review proposes a “Sprint vs. Marathon” framework to explain how viral life cycles shape distinct metabolic hijacking styles. Acute RNA viruses employ a rapid, high-intensity “Sprint” strategy, aggressively activating glycolysis through pathways such as PI3K/Akt and HIF-1α. In contrast, chronic and latent viruses adopt a sustained “Marathon” strategy, subtly modulating glycolytic enzymes, glucose transporters, and survival pathways including NF-κB and mTOR. Understanding these divergent metabolic programs provides new insight into viral pathogenesis and highlights opportunities for developing host-directed antiviral therapies.